Discourse and Collaboration: The Role of Conversations and Collective Identity - Hardy, Cynthia; Lawrence, Thomas B.; Grant, David (Academy of Management Review, 2005)
We explore the relationship between discourse and interorganizational collaboration, arguing that interorganizational collaboration can be understood as the product of sets of conversations that draw on existing discourses. Specifically, we argue that effective collaboration, which we define as cooperative, interorganizational action that produces innovative, synergistic solutions and balances divergent stakeholder concerns, emerges out of a two-stage process. In this process conversations produce discursive resources that create a collective identity and translate it into effective collaboration.